2014
DOI: 10.1016/j.pediatrneurol.2013.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Stimulant Use in Patients With Sturge-Weber Syndrome: Safety and Efficacy

Abstract: BACKGROUND Sturge Weber Syndrome (SWS) is characterized by a facial port-wine birthmark, vascular eye abnormalities, and a leptomeningeal angioma. Attention and behavioral issues are common in SWS; however, literature evidence for stimulant treatment is minimal. This study evaluates stimulant medication safety and efficacy in SWS patients. METHODS The research database of the Hunter Nelson Sturge-Weber Center (n = 210 subjects with SWS brain involvement) was reviewed for stimulant use. Twelve subjects (mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…7 Attention deficit hyperactivity disorder (ADHD) occurs in about 40% of patients with SWS. 30 In another study, stimulants were subjectively assessed to be effective ADHD treatments in SWS with minimal side effects. 30 Neuropsychological testing beginning at age 3 or 4 years can be helpful in identifying high-risk children 31 so that proper interventions, including early initiation of an individualized education plan and behavioral therapy, can be implemented.…”
Section: Neurologymentioning
confidence: 99%
“…7 Attention deficit hyperactivity disorder (ADHD) occurs in about 40% of patients with SWS. 30 In another study, stimulants were subjectively assessed to be effective ADHD treatments in SWS with minimal side effects. 30 Neuropsychological testing beginning at age 3 or 4 years can be helpful in identifying high-risk children 31 so that proper interventions, including early initiation of an individualized education plan and behavioral therapy, can be implemented.…”
Section: Neurologymentioning
confidence: 99%
“…Patients with cognitive deficits and attention problems can benefit from specialized education services, behavioral psychology intervention, and stimulant use. Stimulants have been shown to positively impact attention problems in SWS patients [55]. To address hemiparesis, physical and occupational therapy can be incorporated at an early age to improve motion and fine motor skills; some work with constraint therapy has been done with these patients and has been shown to be helpful [56].…”
Section: Treatmentmentioning
confidence: 99%
“…Finally, 48 articles met all the inclusion criteria and were included in the systematic review. Among these, 37 were case reports or case series , seven were retrospective observational studies based on medical records (45)(46)(47)(48)(49)(50)(51) and four studies were conducted using observational questionnaires (52)(53)(54)(55). The flow diagram of the study selection process according to the PRISMA guidelines is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%